Phloem exudate metabolic content reflects the response to water-deficit stress in pea plants (Pisum sativum L.) - Blicharz, Sara; Beemster, Gerrit T S; Ragni, Laura; De Diego, Nuria; Spíchal, Lukas; Hernándiz, Alba E; Marczak, Łukasz; Olszak, Marcin; Perlikowski, Dawid; Kosmala, Arkadiusz; Malinowski, Robert (The Plant journal, 2021)
Drought stress impacts the quality and yield of Pisum sativum. Here, we show how short periods of limited water availability during the vegetative stage of pea alters phloem sap content and how these changes are connected to strategies used by plants to cope with water deficit. We have investigated the metabolic content of phloem sap exudates and explored how this reflects P. sativum physiological and developmental responses to drought. Our data show that drought is accompanied by phloem-mediated redirection of the components that are necessary for cellular respiration and the proper maintenance of carbon/nitrogen balance during stress. The metabolic content of phloem sap reveals a shift from anabolic to catabolic processes as well as the developmental plasticity of P. sativum plants subjected to drought. Our study underlines the importance of phloem-mediated transport for plant adaptation to unfavourable environmental conditions. We also show that phloem exudate analysis can be used as a useful proxy to study stress responses in plants. We propose that the decrease in oleic acid content within phloem sap could be considered as a potential marker of early signalling events mediating drought response.
Keywords: listy rostlin; Plant Exudates; drought; Genotype; Nitrogen; voda; Adaptation, Physiological; uhlík; Droughts; Phloem; Oleic Acid; fyziologická adaptace; Stress, Physiological; Pisum sativum; phloem; biologický transport; rostlinné exsudáty; oleic acid; abiotic stress; Carbon; Plant Leaves; dusík; developmental plasticity; hrách setý; floém; genotyp; fyziologický stres; Water; Biological Transport; období sucha; kyselina olejová